Contemporary linguistics an introduction / William O'Grady John Archibald, Mark Aronoff,Janie- Rees Miller - O'Grady, William Archibald, John Aronoff, Mark Miller Janie- Rees (2010)
Language: a preview, phonetics:the sounds of language